The Influence of ESG and Dividend Policy on Firm Value: The Moderating Role of Financial Performance in Multinational Consumer Goods Companies Listed in Indonesia and Malaysia (2019–2023) - Misrudi, Misrudi; Tatariyanto, Firman; Nofryanti, Nofryanti (Majalah Ilmiah Bijak, 2025)
This study aims to test whether there is an influence of Environment, Social and Governance (ESG) and Dividend Policy on Company Value (PBV) with Financial Performance (ROA) as a moderating variable. This study uses samples of Indonesian and Malaysian manufacturing companies respectively during the period 2019-2023. The sample was taken using a purposive sampling method, so the number of samples used in this study was 125 financial reports and sustainability reports from 25 (Indonesia 18 and Malaysia 7) manufacturing companies during the period 2019-2023. Hypothesis testing used in the study uses panel data regression analysis and moderated regression analysis (Moderated Regression Analysis) with the help of E-VIEWS software. The results of the hypothesis test prove that in Indonesia ESG and dividend policy have no effect on PBV. However, there are differences in Indonesia and Malaysia. Then the results of the test together (Indonesia and Malaysia) ROA is unable to strengthen ESG against PBV and ROA is able to strengthen Dividend Policy against PBV.